Association between glycosylated hemoglobin and newly diagnosed hypertension in a non-diabetic kosovar population: a cross-sectional analysis - Arber Dreshaj; Altin Dreshaj; D. Veseli; D. Sinanaj; A. Bresa; E. Morina; Sh. Dehari (Medičnì Perspektivi)
Diabetes mellitus is a common disease followed by cardiovascular complications, it is a metabolic syndrome with multiple etiology that is characterized by chronic hyperglycemia. Hypertension is a serious health condition that is significantly associated with the risks of heart, brain, kidney, and other diseases. Glycosylated hemoglobin (HbA1c) is diagnostic means of diabetes when fasting (venous) glycemia figures are 126 mg/dl (7.0 mmol/l). The purpose of this study is to focus on the diagnosis, and the treatment of the population with diabetes, identifying the necessary targets to guarantee clinical efficacy. Managing diabetes is challenging, and smoking can complicate it. People with diabetes who smoke often need larger doses of insulin to keep their blood sugar near normal levels. To assess the amount of vitamin D bound to hemoglobin, the study analyzed a number of laboratory parameters in patients with type 2 diabetes. The importance of this study is the estimation of the amount of enzyme-linked immunosorbent vitamin D. Laboratory parameters of diabetic patients were divided into three categories based on increased levels of glycosylated hemoglobin. Vitamin D levels were analyzed in these categories with increased HbA1c values. The influence of smoking and hypertension on laboratory parameters of diabetic patients was analyzed. The observations were carried out in the form of a database, and the methods that allowed the results for all parameters were followed. The data on the homogeneity of the selected information groups cover 150 patients diagnosed with diabetes mellitus, 40.67% were men, 59.33% were women. Similarly, (in fasting patients), a high OGTT-2-hour glucose level, the hemoglobin test indicates [A1C(HbA1c)] level, cardiovascular disease, and serum vitamin D. Overall, 47.33% of the patients were deficient in vitamin D. Decreased levels of vitamin D were associated with increased levels of glycosylated hemoglobin, while 22% were deficient. As a result, 74.67% of tobacco users had hypertension. Vitamin D deficiency may increase in patients with diabetes, with increased levels of glycosylated hemoglobin.